Sulfide solid electrolyte powder and electrode mixture

A sulfide solid electrolyte powder with a specific strain value and surface area relationship, combined with an argyrodite crystal structure and amorphous phase, addresses the challenge of maintaining interfacial contact in all-solid-state batteries at low pressures, enhancing battery performance and durability.

JP2025009725AActive Publication Date: 2025-01-20AGC INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023210179
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-12-13
Publication Date
2025-01-20
Estimated Expiration
2043-07-05

AI Technical Summary

Technical Problem

Existing all-solid-state batteries require high confining pressure to maintain interfacial contact between the positive and negative electrode active materials and the solid electrolyte, which leads to decreased battery capacity due to volume changes during charge-discharge cycles.

Method used

A sulfide solid electrolyte powder with a specific strain value and specific surface area relationship, combined with an argyrodite crystal structure, is used to maintain good interfacial contact at low confining pressures, incorporating a certain amount of amorphous phase to enhance elastic deformation.

Benefits of technology

The sulfide solid electrolyte powder maintains good interfacial contact and suppresses battery deterioration during repeated charge-discharge cycles, allowing for the production of all-solid-state batteries without the need for large restraint jigs and preserving battery characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009725000002
    Figure 2025009725000002
  • Figure 2025009725000001
    Figure 2025009725000001
Patent Text Reader

Abstract

To provide a sulfide solid electrolyte powder that can maintain good interface contact with an active material even under low confinement pressure when used in a solid-state battery.SOLUTION: The present invention relates to a sulfide solid electrolyte powder that has a crystal phase, where a value expressed by {[(strain value)-0.001] / [specific surface area (m2 / g)]}×100 is 0.010-0.070, and the crystal phase has an argyrodite crystal structure.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sulfide solid electrolyte powder and an electrode mixture containing the same. [Background technology]

[0002] Lithium ion secondary batteries are widely used in portable electronic devices such as mobile phones and notebook computers. Conventionally, liquid electrolytes have been used in lithium-ion secondary batteries, but all-solid-state lithium-ion batteries (hereinafter also referred to as solid-state batteries), which use solid electrolytes as the electrolyte for lithium-ion secondary batteries, are attracting attention because of the potential for improved safety and high-speed charging and discharging.

[0003] Solid electrolytes are broadly classified into sulfide solid electrolytes and oxide solid electrolytes. Among them, sulfide solid electrolytes exhibit high ionic conductivity because they contain sulfide ions with high polarizability. As a sulfide solid electrolyte, Li 10 GeP2S 12 LGPS-type crystals such as Li6PS5Cl, argyrodite-type crystals such as Li7P3S 11 Crystallized glass such as LPS crystallized glass is known.

[0004] When manufacturing an all-solid-state battery such as a lithium-ion battery using the above-mentioned sulfide solid electrolyte, it is necessary to use a high restraining pressure in order to maintain interfacial contact between the positive electrode active material or negative electrode active material and the solid electrolyte during charging and discharging. This is to prevent the good interfacial contact from being impaired due to volume changes caused by expansion and contraction of the positive electrode active material or negative electrode active material accompanying charging and discharging of the all-solid-state battery. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2021 / 085239 Summary of the Invention [Problem to be solved by the invention]

[0006] In order to achieve such a high confinement pressure, it is necessary to use a large confinement jig. Even if an all-solid-state battery is obtained at a high confinement pressure, the volume changes as the charge-discharge cycle is repeated, making it difficult to maintain good interfacial contact, and the battery capacity decreases.

[0007] Therefore, an object of the present invention is to provide a sulfide solid electrolyte powder that can maintain good interfacial contact with an active material even under low restraint pressure when used in an all-solid-state battery, and an electrode mixture containing the same. [Means for solving the problem]

[0008] Patent Document 1 discloses a solid electrolyte containing a crystalline phase having an argyrodite-type crystal structure, and discloses that the lattice distortion of the compound having the crystalline phase is less than 0.10%, and that the smaller the lattice distortion, the more improved the lithium ion conductivity. In response to this, the present inventors conducted extensive research and found that the above-mentioned problems can be solved by imparting a certain degree of distortion to a crystal phase constituting a sulfide solid electrolyte powder and by having a certain relationship with the specific surface area, and thus completed the present invention.

[0009] That is, the present invention relates to the following. [1] A sulfide solid electrolyte powder having a crystalline phase, [(distortion value - 0.001) / specific surface area (m 2 / g) × 100 is 0.010 to 0.070, The sulfide solid electrolyte powder, wherein the crystal phase has an argyrodite-type crystal structure. [2] Further having an amorphous phase; The sulfide solid electrolyte powder according to [1] above, wherein the content of the amorphous phase is 5 mass % or more. [3] The sulfide solid electrolyte powder according to [1] or [2], wherein the argyrodite-type crystal structure contains two or more halogen elements as constituent elements. [4] The halogen element contains Br, The content ratio of Br to the halogen element is 0.1 to 0.9, and the sulfide solid electrolyte powder according to [3] above. [5] The alditol-type crystal structure is Li a MZ b Ha c represented by the composition formula of, In the composition formula, M is at least one element selected from Na, K, and elements existing as divalent to pentavalent cations in the crystal structure, Z is at least one element selected from elements existing as divalent anions in the crystal structure, and Ha is at least one element selected from the group consisting of F, Cl, Br, and I. The composition formula satisfies the relationships of 5 ≦ a ≦ 7, 4 ≦ b ≦ 6, and 1 < c ≦ 2, and the sulfide solid electrolyte powder according to any one of [1] to [4] above. [6] The complex elastic modulus is 5 to 20 GPa, and the sulfide solid electrolyte powder according to any one of [1] to [5] above. [7] An electrode binder containing the sulfide solid electrolyte powder according to any one of [1] to [6] above.

Advantages of the Invention

[0010] According to the present invention, when a all-solid-state battery is formed, a sulfide solid electrolyte powder capable of maintaining good interfacial contact with the active material even at a low restraint pressure can be obtained. Therefore, a all-solid-state battery can be manufactured without using a large restraint jig, and a all-solid-state battery with suppressed deterioration of battery characteristics when repeating charge and discharge cycles can be obtained.

Brief Description of the Drawings

[0011] [Figure 1] FIG. 1 is a flowchart showing a method for manufacturing the sulfide solid electrolyte powder according to the present embodiment.

Embodiments for Carrying Out the Invention

[0012] The present invention will be described in detail below, but the present invention is not limited to the following embodiments and can be modified as desired without departing from the gist of the present invention. In addition, the symbol "to" indicating a numerical range is used to mean that the numerical values ​​before and after the symbol are included as the lower and upper limits.

[0013] 《Sulfide solid electrolyte powder》 The sulfide solid electrolyte powder according to the present embodiment has a crystalline phase, and the crystalline phase has an argyrodite-type crystal structure. In addition, the sulfide solid electrolyte powder has a ratio of [(distortion value - 0.001) / specific surface area (m 2 / g) × 100 is 0.010 to 0.070.

[0014] Here, the above-mentioned distortion value means a disorder in the crystal structure. Specifically, a state in which the average coordinates of each atom in a crystal structure are constant but each coordinate has a distribution is called a disorder in the crystal structure and is quantified by a distortion value. The inventors have found that by increasing the above-mentioned disorder in the sulfide solid electrolyte powder, it is possible to suppress the deterioration of battery characteristics associated with the volume change of the active material due to expansion and contraction during charging and discharging.

[0015] Although the reason for this is unclear, it is believed that the above-mentioned crystal structure disorder makes it easier for the coordinates of each atom in the crystal structure of the sulfide solid electrolyte powder to shift in accordance with the volume change of the active material that accompanies charging and discharging, which results in good interfacial contact between the active material and the sulfide solid electrolyte powder. Due to such a disorder in the crystal structure, the coordinates of each atom become more easily displaced, and this absorbs the volumetric change of the active material, that is, it can be said that the elastic deformation region becomes wider.

[0016] The crystal structure disorder in the sulfide solid electrolyte powder can be quantified as a distortion value in structural analysis of the powder X-ray diffraction (XRD) pattern, with a higher distortion value indicating a greater degree of crystal structure disorder.

[0017] Specifically, the above-mentioned strain value is obtained by analysis using the Williamson-Hall method for the XRD pattern.

[0018] The strain value of the sulfide solid electrolyte powder according to the present embodiment is preferably large from the viewpoint of maintaining good interface contact. In addition, it has been found that when the sulfide solid electrolyte is pulverized to reduce the particle size of the sulfide solid electrolyte powder and increase the specific surface area, the specific surface area and the strain value show a positive correlation. That is, the larger the specific surface area, the larger the strain value. On the other hand, the larger the specific surface area of ​​the sulfide solid electrolyte powder is, the smaller the ionic conductivity tends to be. Therefore, in order to obtain good battery characteristics, it is not enough to simply increase the strain value.

[0019] As a result of further investigation, the inventors have come to the conclusion that if the strain value of a sulfide solid electrolyte powder can be made larger than that of a conventional powder for the same specific surface area, the problems of the present invention can be solved while maintaining good ionic conductivity. As a result of further investigation, the inventors have found that the problems of the present invention can be solved and good battery characteristics can be achieved when the strain value and the specific surface area satisfy a certain relationship, and have actually obtained a sulfide solid electrolyte that satisfies such characteristics.

[0020] Specifically, [(distortion value - 0.001) / specific surface area (m 2 / g) × 100 is set to 0.010 to 0.070. Here, the value of 0.001 in the above formula is an approximate value of the distortion value of the sulfide solid electrolyte before it is pulverized into powder, and is a value that the present inventors arrived at through their studies.

[0021] In order to increase the distortion value of the sulfide solid electrolyte powder, if the conventional pulverization method is used and the pulverization conditions are made stricter or the pulverization is carried out for a long time, the specific surface area becomes too large due to over-pulverization. As a result, the ion conductivity decreases and good battery characteristics cannot be achieved. In this case, [(distortion value - 0.001) / specific surface area (m 2 / g) × 100 is less than 0.010.

[0022] In response to this, the present invention has arrived at the idea of ​​sequentially performing coarse pulverization, heat treatment, and wet pulverization using a bead mill on the sulfide solid electrolyte, as described below, and has found that this makes it possible to increase the distortion value of the resulting sulfide solid electrolyte powder, even if the increase in specific surface area due to pulverization is smaller than in the past, i.e., even if the pulverization is not as advanced as in the past.

[0023] The sulfide solid electrolyte powder according to this embodiment has a [(distortion value - 0.001) / specific surface area (m 2 The value represented by (a) x 100 is 0.010 to 0.070, preferably 0.015 to 0.060, and more preferably 0.020 to 0.050. From the viewpoint of more effectively obtaining the effects of the present invention, the value is preferably 0.015 or more, and more preferably 0.020 or more. On the other hand, although the upper limit of the above value is not particularly set, the upper limit is set to 0.070 from the viewpoint of maintaining the crystal structure and ionic conductivity. From the above viewpoint, the above value is preferably 0.060 or less, and more preferably 0.050 or less.

[0024] The distortion value of the sulfide solid electrolyte powder is [(distortion value - 0.001) / specific surface area (m 2 The value expressed by the formula (100) × 100 is not particularly limited as long as it is within the range of 0.010 to 0.070. The above-mentioned strain value is, for example, preferably 0.0020 to 0.0080, more preferably 0.0030 to 0.0070, and even more preferably 0.0040 to 0.0060. Here, from the viewpoint of maintaining a better interface contact with the active material even under low restraining pressure, the strain value is preferably 0.0020 or more, more preferably 0.0030 or more, and even more preferably 0.0040 or more. In addition, from the viewpoint of maintaining a high ion conductivity, the strain value is preferably 0.0080 or less, more preferably 0.0070 or less, and even more preferably 0.0060 or less.

[0025] The specific surface area of ​​the sulfide solid electrolyte powder is [(distortion value - 0.001) / specific surface area (m 2There is no particular limitation as long as the value expressed by [(1 / g)×100] is within the range of 0.010 to 0.070. The specific surface area is, for example, 4 to 35 m 2 / g is preferable, and 7 to 30m 2 / g is more preferable, and 13 to 20m 2 From the viewpoint of forming more interfaces with the active material and further improving the battery characteristics, the specific surface area is preferably 4 m 2 / g or more is preferable, and 7m 2 / g or more is more preferable, and 13m 2 From the viewpoint of suppressing the decrease in ion conductivity due to the fine particle size, the specific surface area is preferably 35 m 2 / g or less is preferable, and 30m 2 / g or less is more preferable, and 20m 2 / g or less is more preferable. In this specification, the specific surface area is a value called BET specific surface area, which is determined by a nitrogen adsorption BET multipoint method.

[0026] The sulfide solid electrolyte powder according to the present embodiment has a crystal phase having an argyrodite-type crystal structure. Here, the argyrodite-type crystal structure is a crystal structure possessed by a group of compounds derived from a mineral represented by the composition formula Ag8GeS6. The sulfide solid electrolyte powder according to the present embodiment is not limited to the above crystal structure, and some elements may be substituted with other elements.

[0027] When the sulfide solid electrolyte powder according to the present embodiment has an argyrodite-type crystal structure, it preferably contains a halogen (Ha) element as a constituent element, more preferably contains two or more kinds of Ha elements. It is more preferable that the Ha element contains at least one element selected from the group consisting of Cl, Br, and I, and further preferably contains two or more elements.

[0028] The argyrodite-type crystal structure in this embodiment more preferably contains at least one of Cl and Br as the Ha element, and further preferably contains Cl and Br.

[0029] When the above-mentioned alluaudite-type crystal structure contains two or more halogen elements, one of them is preferably Br, and the content ratio of Br to the halogen elements is more preferably 0.1 to 0.9, even more preferably 0.2 to 0.8, and still more preferably 0.3 to 0.7. Here, the content ratio of the above-mentioned Br is preferably 0.1 or more, more preferably 0.2 or more, and even more preferably 0.3 or more from the viewpoint of improving the ionic conductivity. Also, from the viewpoint of suppressing the decrease in ionic conductivity, the content ratio of the above-mentioned Br is preferably 0.9 or less, more preferably 0.8 or less, and even more preferably 0.7 or less.

[0030] The alluaudite-type crystal structure preferably has the above structure, but the composition formula is Li a MZ b Ha c and it is preferably represented by and satisfies the relationships of 5 ≦ a ≦ 7, 4 ≦ b ≦ 6 and 1 < c ≦ 2.

[0031] In the above composition formula, M represents at least one element selected from Na, K, and elements existing as divalent to pentavalent cations in the crystal structure. Also, Z represents at least one element selected from elements existing as divalent anions in the crystal structure. Further, Ha represents a halogen element.

[0032] Here, among M in the above composition formula, examples of the elements existing as divalent to pentavalent cations specifically include B, Mg, Al, Si, P, Ca, Ti, V, Fe, Zn, Ga, Sr, Y, Zr, Nb, Mo, Sn, Sb, Ba, Ta, W, and Bi.

[0033] From the viewpoint of the oxidation-reduction potential of the element, it is preferable that the above M mainly contains P. Specifically, M mainly contains P means that the ratio of the content of P (at%) to the content of M (atoms%, hereinafter referred to as "at%)) in the argyrodite-type crystal structure is 0.6 or more, and the above ratio is preferably 0.6 to 1. The above ratio is more preferably 0.7 or more, and further preferably 0.8 or more. In addition, the upper limit of the above ratio is not particularly limited, and may be 1, 0.98 or less, 0.97 or less, or 0.95 or less.

[0034] The above M may contain, in addition to P, at least one element selected from Na, K, Mg, and Ca. A mixture containing lithium sulfide (Li2S) may be preferably used as a raw material for forming an argyrodite-type crystal structure. Here, it is widely known that lithium sulfide is produced from lithium hydroxide (LiOH), which may contain at least one element selected from the group consisting of Na, K, Mg, and Ca (hereinafter, also referred to as "R") as an impurity. That is, M may contain R derived from such impurities in the raw material.

[0035] In order to reduce the content of R derived from impurities, raw materials with high purity may be required, which raises concerns about increased manufacturing costs. The ratio of the content (at%) of R to the content (at%) of M is preferably 0.001 to 0.4, and more preferably 0.01 to 0.3. From the viewpoint of suppressing the production cost, the ratio is preferably 0.001 or more, more preferably 0.01 or more, and even more preferably 0.02 or more. From the viewpoint of suppressing the decrease in lithium ion conductivity, the ratio is preferably 0.4 or less, and more preferably 0.3 or less.

[0036] It should be noted that the above range does not in any way preclude intentionally incorporating R into the argyrodite-type crystal structure or precludes the inclusion of R in a larger amount than the above-mentioned ratio. For example, in the above composition formula showing an argyrodite type crystal structure, when Z contains O, R contains at least one element selected from Al, Ca, Mg, Na and K, and the element is M. n+ It is preferable that M is present at the Li site as n+ represents a monovalent to trivalent cation. In this case, it is more preferable that the R contains Al. In this case, the content (at %) of R relative to the content (at %) of M may be higher than the above range.

[0037] In the above composition formula, Z is at least one element selected from elements that exist as a divalent anion in the crystal structure, and examples thereof include S, O, Se, and Te. Among these, from the viewpoint of lithium ion conductivity, it is preferable that Z mainly contains S. Specifically, Z mainly contains S means that the ratio of the S content (at%) to the Z content (at%) in the crystal structure is 0.6 or more, and the ratio is preferably 0.6 to 1. The ratio is more preferably 0.7 or more, and further preferably 0.8 or more. In addition, the upper limit of the ratio is not particularly limited, and may be 1, 0.98 or less, 0.95 or less, or 0.9 or less.

[0038] Furthermore, when the above Z contains S, a part of S may be substituted with Ha, BH4, CN, or the like in addition to the above O, Se, and Te.

[0039] In the above composition formula, the halogen element represented by Ha is preferably at least one element selected from the group consisting of F, Cl, Br, and I. From the viewpoint of easiness of forming an argyrodite-type crystal structure, the above Ha preferably contains at least one of Cl and Br, more preferably contains Br, and further preferably is Br alone or a mixture of Cl and Br. From the viewpoint of further improving the lithium ion conductivity, Ha is preferably a mixture of Cl and Br.

[0040] In the case where Ha contains Cl and Br, the Cl content in the argyrodite-type crystal structure is x (at%) and the Br content is y (at%), then the ratio represented by (x / y) is preferably 0.1 to 10, more preferably 0.3 to 3, and even more preferably 0.5 to 1.6. Here, the ratio is preferably 0.1 or more, more preferably 0.3 or more, and even more preferably 0.5 or more, and is preferably 10 or less, more preferably 3 or less, and even more preferably 1.6 or less. When the ratio (x / y) satisfies the above range, the interaction between lithium ions and halide ions is weakened, and the lithium ion conductivity is likely to be good. This is thought to be due to the mixed anion effect, which weakens the interaction between cations and anions by mixing bromide ions, which have a larger ionic radius than chloride ions. In addition, the cycle characteristics of lithium ion secondary batteries are also likely to be improved.

[0041] When Ha contains Cl and Br, the ratio of the content (at%) of the elements constituting the argyrodite-type crystal structure is Li a MZ b Cl c1 Br c2 In this case, c1 is preferably 0.1 to 1.5, more preferably 0.3 to 1.4, and even more preferably 0.5 to 1.3. Here, c1 is preferably 0.1 or more, more preferably 0.3 or more, and even more preferably 0.5 or more, and is preferably 1.5 or less, more preferably 1.4 or less, and even more preferably 1.3 or less. Moreover, the above-mentioned c2 is preferably 0.1 to 1.9, more preferably 0.3 to 1.6, and further preferably 0.5 to 1.4. Here, c2 is preferably 0.1 or more, more preferably 0.3 or more, and further preferably 0.5 or more, and is preferably 1.9 or less, more preferably 1.6 or less, and further preferably 1.4 or less. When c1 and c2 each satisfy the above ranges, the proportion of halide ions in the crystal is optimized, and a stable argyrodite-type crystal can be obtained while reducing the interaction between anions and lithium ions in the crystal structure. As a result, the lithium ion conductivity of the sulfide solid electrolyte powder tends to be good. In addition, when c1 and c2 satisfy the above ranges, the cycle characteristics of the lithium ion secondary battery tend to be improved. In addition, Li a MZ b Cl c1 Br c2 In the composition formula represented by, it is preferable that a, b, and (c1 + c2) satisfy the same relationship as a, b, and c described below.

[0042] The above Li a MZ b Ha c Regarding the ratio of each element in the composition formula represented by, it is preferable to satisfy the relationship of 5 ≤ a ≤ 7, 4 ≤ b ≤ 6, and 1 < c ≤ 2. More preferably, it satisfies the relationship of 5 < a < 7, 4 < b < 6, and 1 < c < 2. Even more preferably, it satisfies the relationship of 5.1 < a < 6.3, 4 < b < 5.3, and 1.4 ≤ c ≤ 1.9. Even more preferably, it satisfies the relationship of 5.2 < a < 6.2, 4.1 < b < 5.2, and 1.5 ≤ c ≤ 1.8.

[0043] That is, for a, 5 or more is preferable, more than 5 is more preferable, more than 5.1 is even more preferable, more than 5.2 is even more preferably. Also, 7 or less is preferable, less than 7 is more preferable, less than 6.3 is even more preferable, less than 6.2 is even more preferably. For b, 4 or more is preferable, more than 4 is more preferable, more than 4.1 is even more preferable. Also, 6 or less is preferable, less than 6 is more preferable, less than 5.3 is even more preferable, less than 5.2 is even more preferably. For c, more than 1 is preferable, 1.3 or more is more preferable, 1.4 or more is even more preferable, 1.5 or more is even more preferably. Also, 2 or less is preferable, less than 2 is more preferable, less than 1.9 is even more preferable, less than 1.8 is even more preferably.

[0044] The crystal structure of the argyrodite type is, for example, a cubic crystal (e.g., F-43m), but less symmetrical crystals such as hexagonal, tetragonal, orthorhombic, monoclinic, and even less symmetrical crystals such as triclinic may also exist.

[0045] The sulfide solid electrolyte powder according to this embodiment contains a crystalline phase, and the content ratio (crystallinity) of the crystalline phase is preferably 50 to 100 mass%, more preferably 60 to 99 mass%, even more preferably 65 to 95 mass%, and even more preferably 70 to 90 mass%. From the viewpoint of ensuring lithium ion conductivity, the content is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 65% ​​by mass or more. On the other hand, the content may be 100% by mass, i.e., the material may be composed of only a crystalline phase, but from the viewpoint of obtaining the effect of expanding the elastic deformation region due to the presence of an amorphous phase, the content is preferably 99% by mass or less, more preferably 95% by mass or less, and even more preferably 90% by mass or less.

[0046] The crystal phase in this embodiment may have a crystal phase having a crystal structure other than the argyrodite type, but the proportion of the crystal phase having the argyrodite type crystal structure to the entire crystal phase is preferably 50 mass% or more, more preferably 80 mass% or more, and the higher the better. The crystal phase that may be present other than the argyrodite-type crystal structure is, for example, Li7P3S 11 The crystalline phases having a crystal structure containing Li, P, and S elements, which are called LPS systems, such as Li 10 GeP2S 12 Examples of such a crystal phase include a crystal phase having a crystal structure containing Li, Ge, P, and S elements, which is called an LGPS system, such as a crystalline phase having a thiolicon type crystal structure, and a crystal phase containing an oxide.

[0047] The sulfide solid electrolyte powder according to this embodiment may contain an amorphous phase. The presence of the amorphous phase is preferable because it expands the elastic deformation region. The composition of the amorphous phase is generally the same as that of the crystalline phase. Details of the elastic deformation region will be described below.

[0048] The content of the amorphous phase in the sulfide solid electrolyte powder is preferably 5% by mass or more, more preferably 5 to 50% by mass, even more preferably 10 to 40% by mass, and even more preferably 15 to 30% by mass. From the viewpoint of more effectively utilizing the presence of the amorphous phase, the content is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more. From the viewpoint of maintaining ion conductivity, the content is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less. The crystal structure and content of the crystal phase in the sulfide solid electrolyte powder can be determined by analyzing the XRD pattern. The content of the amorphous phase can be determined by subtracting the amount of the amorphous phase from the content of all the crystal phases by analyzing the XRD pattern.

[0049] The sulfide solid electrolyte powder according to the present embodiment has a high elastic modulus compared to those having a low strain value. Specifically, a pellet having a relative density of 90% is prepared using the sulfide solid electrolyte powder, and the composite elastic modulus measured by a nanoindentation test using a spherical indenter with a tip radius of 100 μm can be, for example, 5 GPa or more.

[0050] In general, crystalline solid electrolytes have a small elastic deformation range and cannot absorb the volume change of the active material that occurs during charging and discharging. Therefore, it is necessary to fabricate all-solid-state batteries with high confinement pressure and maintain the contact interface between the solid electrolyte and the active material. However, even when high confinement pressure is used, the solid electrolyte material gradually undergoes plastic deformation when repeatedly charged and discharged, resulting in a decrease in cycle characteristics. In contrast, the sulfide solid electrolyte powder according to the present embodiment is believed to have an expanded elastic deformation region due to the disturbance of the crystal structure, i.e., distortion. The inclusion of an amorphous phase is also believed to expand the elastic deformation region. As a result, even when an all-solid-state battery is produced at a low restraining pressure, the contact interface between the solid electrolyte and the active material is maintained, good battery characteristics are obtained, and the deterioration of cycle characteristics can also be suppressed.

[0051] In this embodiment, the composite elastic modulus is preferably 5 GPa or more, more preferably 5 to 20 GPa, even more preferably 7 to 18 GPa, and even more preferably 10 to 15 GPa. From the viewpoint of obtaining better battery characteristics, the composite elastic modulus is preferably 20 GPa or less, more preferably 18 GPa or less, and even more preferably 15 GPa or less, and the lower the better. On the other hand, in reality, the composite elastic modulus may be 5 GPa or more, 7 GPa or more, or 10 GPa or more.

[0052] Since the particle size D50 of the sulfide solid electrolyte powder according to this embodiment correlates with the BET specific surface area, the particle size D50 is adjusted so as to obtain a suitable BET specific surface area. For example, 2 / g, the particle size D50 is about 0.4 μm or more and less than 1.0 μm. In this specification, the particle size D50 is the volume-based cumulative 50% diameter determined by a laser diffraction particle size distribution measuring device. That is, the particle size distribution is measured by a laser diffraction / scattering method, a cumulative curve is calculated with the total volume of the sulfide solid electrolyte as 100%, and the particle size D50 is the particle size at the point on the cumulative curve where the cumulative volume is 50%.

[0053] The BET specific surface area and particle size D50 of the sulfide solid electrolyte powder can be adjusted by the grinding method and grinding conditions when the sulfide solid electrolyte is ground to form the sulfide solid electrolyte powder. One method for pulverizing sulfide solid electrolytes is to use a bead mill. It has been found that this method can increase the strain value to a desired level without making the particle size D50 too small.

[0054] The crystallite diameter in the argyrodite-type crystal structure in the sulfide solid electrolyte powder according to this embodiment is preferably 100 to 3000 Å, more preferably 200 to 2500 Å, and even more preferably 300 to 2000 Å. Here, from the viewpoint of ion conductivity, the crystallite diameter is preferably 100 Å or more, more preferably 200 Å or more, and even more preferably 300 Å or more. In addition, considering that the crystallite diameter inevitably becomes smaller when the particle size is made finer, from the viewpoint of realizing the particle size D50 and BET specific surface area desired for the sulfide solid electrolyte powder, the crystallite diameter is preferably 3000 Å or less, more preferably 2500 Å or less, and even more preferably 2000 Å or less. In this specification, the crystallite size is a value determined together with the strain value when the XRD pattern of the sulfide solid electrolyte powder is analyzed by the Williamson-Hall method.

[0055] The lithium ion conductivity of the sulfide solid electrolyte powder according to this embodiment is preferably 0.1 mS / cm or more, more preferably 0.5 mS / cm or more, even more preferably 1.0 mS / cm or more, and particularly preferably 1.5 mS / cm or more, from the viewpoint of obtaining good battery characteristics when used in a lithium ion secondary battery. The higher the conductivity, the better. The upper limit of the lithium ion conductivity is not particularly limited, but is, for example, 15 mS / cm.

[0056] In this specification, the lithium ion conductivity is a value obtained by measuring a measurement sample obtained by applying a pressure of 380 MPa to the sulfide solid electrolyte powder and compacting it with an AC impedance measuring device. Here, the measurement conditions for the AC impedance measurement are a measurement frequency of 100 Hz to 1 MHz, a measurement voltage of 100 mV, and a measurement temperature of 25°C.

[0057] The sulfide solid electrolyte powder according to the present embodiment is suitably used in an all-solid-state lithium ion secondary battery by treating the sulfide solid electrolyte powder according to the present embodiment by a conventionally known method as desired, and then applying pressure together with a positive electrode active material or a negative electrode active material to form a positive electrode layer or a negative electrode layer, which is an electrode mixture, or by applying pressure together with an additive such as a binder as necessary to form a solid electrolyte layer.

[0058] <Method of manufacturing sulfide solid electrolyte powder> As shown in FIG. 1, the method for producing the sulfide solid electrolyte powder according to this embodiment includes the following steps in order. Step 1: Preparing a sulfide solid electrolyte Step 2: Step S1: Coarsely pulverizing the sulfide solid electrolyte to obtain a coarsely pulverized sulfide solid electrolyte. Step 3: Step S2: Obtaining a powder by heat-treating the coarsely pulverized material while suppressing aggregation. Step 4: Step S3: finely pulverizing the heat-treated powder to obtain a sulfide solid electrolyte powder.

[0059] Each step will be described below in order.

[0060] ·Process 1 Step 1 is a step of preparing a sulfide solid electrolyte. The sulfide solid electrolyte may be synthesized or may be a commercially available one. When synthesizing the sulfide solid electrolyte, a conventionally known method may be adopted, but a melting method is preferred from the viewpoint of obtaining a sulfide solid electrolyte with a high distortion value.

[0061] When synthesizing a sulfide solid electrolyte, it is preferable to include, for example, a step of obtaining a raw material mixture, a step of reacting the raw material mixture, and a step of crystallizing or amorphizing the raw material mixture.

[0062] The reaction in the step of reacting the raw material mixture may be a thermal reaction or a mechanochemical reaction. In addition, when the sulfide solid electrolyte is obtained by the thermal reaction, a separate crystallization or amorphization step does not need to be included. In the case of the melting method, the raw materials are mixed as necessary, heated to melt, and then cooled to solidify, thereby obtaining a sulfide solid electrolyte.

[0063] The raw materials vary depending on the desired composition of the crystalline or amorphous phase, but raw materials containing, for example, Li, P, S, and Ha can be used. The above raw materials may each be any of those known in the art. The conditions for mixing and reacting the raw materials may be those known in the art. For example, in the case of a melting method, the heating temperature during heating and melting, the time during heating and melting or cooling and solidifying, the atmosphere, pressure, dew point, and the like may be those known in the art. Alternatively, an intermediate may be used in which the raw materials are reacted before being melted, and melt synthesis may be carried out from the intermediate.

[0064] ·Process 2 Step 2 is a step of roughly pulverizing the sulfide solid electrolyte obtained in step 1 to obtain a roughly pulverized sulfide solid electrolyte (step S1). By performing coarse pulverization before carrying out the heat treatment in step 3 described below, the particle size is made fine to a certain extent. Then, by carrying out the heat treatment in the next step 3 while suppressing aggregation, a sulfide solid electrolyte powder with high ionic conductivity can be obtained. As a result, the load of the further pulverization step thereafter is reduced, the decrease in ionic conductivity can be suppressed, and the process load can also be reduced.

[0065] The method of coarse grinding was as follows: (distortion value - 0.001) / specific surface area (m 2 As long as the value represented by (x / g) × 100 is a desired value, the method is not particularly limited, but a method other than wet grinding is preferable. For example, coarse grinding using a cutter mill (cut mill) can be used. Alternatively, the coarse powder may be obtained by a method of obtaining the coarse powder directly from a melt of the sulfide solid electrolyte.

[0066] A cutter mill is a method of pulverizing raw materials by rotating a rotor equipped with cutters at high speed and using shearing or cutting forces. By performing coarse pulverization using a cutter mill, the sulfide solid electrolyte powder after the heat treatment in the next step 3 while suppressing aggregation and the fine pulverization in step 4 has a [(distortion value - 0.001) / specific surface area (m 2 Thus, it is possible to obtain a sulfide solid electrolyte powder that maintains good interfacial contact with the active material even under low confining pressure.

[0067] As a coarse pulverization method other than the cutter mill, for example, a planetary ball mill, a jet mill, etc. may be adopted, but in this case, dry pulverization without using a dispersion medium is preferable.

[0068] The coarse pulverization is preferably carried out so that the particle size D50 of the coarsely pulverized sulfide solid electrolyte is 5 to 300 μm, more preferably 10 to 200 μm, and even more preferably 10 to 150 μm. From the viewpoint of reducing the load of the fine pulverization step in step 4, the particle size D50 of the coarsely pulverized product is preferably 300 μm or less, more preferably 200 μm or less, and even more preferably 150 μm or less. From the viewpoint of powder handling, the particle size D50 is preferably 5 μm or more, and more preferably 10 μm or more.

[0069] After the sulfide solid electrolyte is coarsely pulverized, classification (sieving, etc.) may be performed as necessary to obtain a coarsely pulverized sulfide solid electrolyte.

[0070] ·Process 3 Step 3 is a step of obtaining a powder by heat treating the coarsely pulverized sulfide solid electrolyte obtained in step 2 while suppressing aggregation (step S2).

[0071] By carrying out the heat treatment, the homogeneity is increased and the quality as a solid electrolyte is stabilized, so that high ionic conductivity can be maintained even if fine pulverization is carried out in the subsequent step 4.

[0072] The heating temperature in the heat treatment is, for example, preferably 200 to 600° C., more preferably 350 to 500° C., further preferably 380 to 460° C., and particularly preferably 400 to 450° C. From the viewpoint of homogenizing the particles and stabilizing the quality, the heating temperature is preferably 200° C. or higher, more preferably 350° C. or higher, further preferably 380° C. or higher, and particularly preferably 400° C. or higher. From the viewpoint of preventing sintering between particles, the heating temperature is preferably 600° C. or lower, more preferably 500° C. or lower, further preferably 460° C. or lower, and particularly preferably 450° C. or lower.

[0073] The heating time in the heat treatment is, for example, preferably 10 minutes to 10 hours, more preferably 30 minutes to 9.5 hours, even more preferably 45 minutes to 9 hours, and particularly preferably 1 to 9 hours. From the viewpoint of homogenizing the particles and stabilizing the quality, the heat treatment time is preferably 10 minutes or more, more preferably 30 minutes or more, even more preferably 45 minutes or more, and particularly preferably 1 hour or more. From the viewpoint of production cost, the heat treatment time is preferably 10 hours or less, more preferably 9.5 hours or less, and even more preferably 9 hours or less.

[0074] The heat treatment is preferably performed in an inert atmosphere, such as a nitrogen gas atmosphere, an argon gas atmosphere, or a helium gas atmosphere.

[0075] Here, in order to perform the heat treatment while suppressing the aggregation of the coarsely pulverized material, it is preferable to perform the heat treatment while flowing the inert gas. The flow rate of the inert gas is, for example, preferably 1 to 1000 L / min, more preferably 5 to 500 L / min, and even more preferably 10 to 100 L / min. Here, from the viewpoint of suitably suppressing the aggregation of the coarsely pulverized material, the flow rate is preferably 1 L / min or more, more preferably 5 L / min or more, and even more preferably 10 L / min or more. Also, from the viewpoint of suppressing the scattering of the coarsely pulverized material, the flow rate is preferably 1000 L / min or less, more preferably 500 L / min or less, and even more preferably 100 L / min or less.

[0076] Furthermore, in addition to the above inert gas, the aggregation can also be suppressed by carrying out the heat treatment in an atmosphere having an SO2 concentration of, for example, 1 to 1000 ppm by volume. Furthermore, agglomeration can also be suppressed by using a container having a low height and a wide bottom during the heat treatment.

[0077] The dew point during the heat treatment is preferably −20° C. or lower, and although there is no particular lower limit, it is usually about −80° C. The oxygen concentration is preferably 1000 ppm by volume or lower.

[0078] In addition, when cooling after the heat treatment, the inert gas is passed through to suppress the aggregation of the coarsely pulverized material. The flow rate of the inert gas in this case is, for example, preferably 1 to 1000 L / min, more preferably 5 to 500 L / min, and even more preferably 10 to 100 L / min. Here, from the viewpoint of suitably suppressing the aggregation of the coarsely pulverized material, the flow rate is preferably 1 L / min or more, more preferably 5 L / min or more, and even more preferably 10 L / min or more. In addition, from the viewpoint of suppressing the scattering of the coarsely pulverized material, the flow rate is preferably 1000 L / min or less, more preferably 500 L / min or less, and even more preferably 100 L / min or less.

[0079] ·Process 4 In step 4, the heat-treated powder obtained in step 3 is pulverized to obtain a sulfide solid electrolyte powder (step S3).

[0080] The fine pulverization is preferably performed using a bead mill. A bead mill is a method of grinding materials into fine powder by rotating hard beads in a cylindrical container. By performing fine pulverization using this method, the distortion value can be increased without excessive pulverization, and the ratio of [(distortion value - 0.001) / specific surface area (m 2 / g) × 100 can be increased.

[0081] That is, the conventional sulfide solid electrolyte powder is crushed to reduce its specific surface area to 15 m 2 / g, the distortion value is 0.0010 or more and less than 0.0020, but the sulfide solid electrolyte powder according to the present embodiment can have a distortion value of 0.0020 or more. Also, for example, to obtain a sulfide solid electrolyte powder with a distortion value of about 0.0025 by pulverization, the specific surface area must be 30 m 2 / g or more, the sulfide solid electrolyte powder according to this embodiment has a specific surface area of ​​10 to 15 m 2 / g.

[0082] The vessel of the bead mill used for fine pulverization may be a conventionally known one, for example, made of alumina (Al2O3), zirconia (ZrO2), or zirconia-reinforced alumina. Examples of the types of beads for fine grinding include alumina beads, zirconia beads, glass beads, etc., and from the viewpoint of wear resistance, zirconia beads, alumina beads, etc. are preferred.

[0083] When zirconia beads are used, yttria-stabilized zirconia is preferable from the viewpoint of increasing fracture toughness.

[0084] When alumina beads are used, high purity alumina beads are preferred from the viewpoint of increasing fracture toughness. The high-purity alumina beads preferably satisfy at least one of a purity of 99.9% or more and a Vickers hardness of 1800HV10 or more, and more preferably satisfy both. By using such high-purity alumina beads, the wear resistance of the beads can be increased and contamination caused by the beads can be suppressed, which is preferable.

[0085] The purity of the alumina beads is preferably 99.9% or more, more preferably 99.93% or more, further preferably 99.95% or more, and particularly preferably 99.99% or more, and the higher the purity the more preferable.

[0086] The Vickers hardness of the alumina beads is preferably 1800HV10 to 2300HV10. From the viewpoint of wear resistance, the Vickers hardness is preferably 1800HV10 or more, more preferably 1900HV10 or more, even more preferably 2000HV10 or more, and particularly preferably 2100HV10 or more. From the viewpoint of suppressing wear of the grinding chamber (vessel) and rotor, the Vickers hardness is preferably 2300HV10 or less.

[0087] The purity of the alumina beads can be determined by measuring the amount of impurities by ICP atomic emission spectrometry and subtracting the total amount of impurities from 100%. The Vickers hardness of an alumina bead can be measured by pressing a pyramidal indenter made of diamond against a test piece, observing the indentation made under a microscope, and measuring the length of the diagonal line.

[0088] In addition, fine powder with a small particle size D50 can be obtained by using a grinding method other than dry grinding or a bead mill, but the BET specific surface area relative to the strain value should not be too large, and the ratio of [(strain value - 0.001) / specific surface area (m 2 From the viewpoint of easily achieving a value represented by the formula (1) (mol / g) × 100 in the range of 0.010 to 0.070, wet grinding using a bead mill is preferred.

[0089] In the wet grinding method, the coarsely ground sulfide solid electrolyte may be dispersed or dissolved in a dispersion medium to form a slurry, and then ground. In addition to the sulfide solid electrolyte solvent, additives such as a dispersant may be further added to the slurry.

[0090] The dispersion medium is not particularly limited, but since the sulfide solid electrolyte has a tendency to react with moisture and deteriorate, a non-aqueous solvent is preferred.

[0091] The type of non-aqueous organic solvent is not particularly limited, and examples thereof include hydrocarbon solvents, organic solvents containing a hydroxy group, organic solvents containing an ether group, organic solvents containing a carbonyl group, organic solvents containing an ester group, organic solvents containing an amino group, organic solvents containing a formyl group, organic solvents containing a carboxy group, organic solvents containing an amide group, organic solvents containing a benzene ring, organic solvents containing a mercapto group, organic solvents containing a thioether group, organic solvents containing a thioester group, organic solvents containing a disulfide group, and alkyl halides.

[0092] Examples of the hydrocarbon solvent include cyclohexane, heptane, octane, and toluene, and from the viewpoint of low saturated water concentration, cyclohexane, heptane, and octane are preferred. From the viewpoint of adjusting the water concentration, it is also preferred to mix these hydrocarbon solvents with toluene, dibutyl ether, or the like to form a mixed solvent.

[0093] In order to prevent a decrease in lithium ion conductivity due to a reaction between the sulfide solid electrolyte and water during fine pulverization of the coarsely pulverized sulfide solid electrolyte, the water concentration in the dispersion medium is preferably low. The water concentration of the dispersion medium may be, for example, 170 ppm by mass or less, 150 ppm by mass or less, 120 ppm by mass or less, or 100 ppm by mass or less.

[0094] When a dispersant is used as the additive, examples of the dispersant include an ether compound, an ester compound, and a nitrile compound.

[0095] The content of the coarsely pulverized sulfide solid electrolyte in the slurry is preferably 5 to 35 mass%, more preferably 10 to 33 mass%, and even more preferably 20 to 30 mass%. From the viewpoint of pulverization efficiency and ease of handling of the slurry, the content is preferably 5 mass% or more, more preferably 10 mass% or more, and even more preferably 20 mass% or more, and is preferably 35 mass% or less, more preferably 33 mass% or less, and even more preferably 30 mass% or less.

[0096] The solid content in the slurry is preferably 5 to 35% by mass, more preferably 10 to 33% by mass, and even more preferably 20 to 30% by mass. From the viewpoint of grinding efficiency and ease of handling of the slurry, the solid content is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 20% by mass or more, and is preferably 35% by mass or less, more preferably 33% by mass or less, and even more preferably 30% by mass or less.

[0097] When the fine grinding is performed by a bead mill, the diameter of the beads for fine grinding is preferably 0.1 to 1 mm, more preferably 0.2 to 0.8 mm, and even more preferably 0.3 to 0.5 mm. Here, from the viewpoint of obtaining a sulfide solid electrolyte powder having good lithium ion conductivity, the diameter is preferably 0.1 mm or more, more preferably 0.2 mm or more, and even more preferably 0.3 mm or more. Also, from the viewpoint of obtaining a finely ground product having a desired small particle size, the diameter is preferably 1 mm or less, more preferably 0.8 mm or less, and even more preferably 0.5 mm or less.

[0098] A drying step may be further carried out on the sulfide solid electrolyte powder obtained in step 4. By drying, even if a dispersion medium or additives remain in the sulfide solid electrolyte powder, they can be removed. The drying method can be a conventionally known method, for example, a hot plate, a drying oven, an electric oven, or the like.

[0099] The temperature in the drying step is not particularly limited, and may be, for example, 50 to 300° C. When fine pulverization is performed using a dispersion medium, drying may be performed by heating at a temperature equal to or higher than the boiling point of the dispersion medium. The time for the drying step is not particularly limited, but may be, for example, 10 minutes to 24 hours. The drying step may be carried out under reduced pressure, for example, at an absolute pressure of 50 kPa or less.

[0100] <Electrode mixture> The sulfide solid electrolyte powder according to the present embodiment may be used for an electrode mixture. That is, the electrode mixture according to the present embodiment contains the sulfide solid electrolyte powder described in the above <Sulfide solid electrolyte powder>, and the preferred aspects of the sulfide solid electrolyte powder are also the same as those described in the above <Sulfide solid electrolyte powder>.

[0101] The electrode mixture according to the present embodiment is preferably used in a lithium ion secondary battery, and is formed by applying pressure to the sulfide solid electrolyte powder together with an active material. That is, when the electrode mixture according to the present embodiment is a negative electrode mixture, it contains at least a negative electrode active material and a sulfide solid electrolyte powder, and when it is a positive electrode mixture, it contains at least a positive electrode active material and a sulfide solid electrolyte powder.

[0102] The active material contained in the electrode mixture can be any known active material. For example, the positive electrode active material is not particularly limited as long as it can reversibly absorb and release lithium ions, remove and insert (intercalate) lithium ions, or dope and dedope a counter anion of the lithium ions. Specific examples include lithium cobaltate, lithium nickelate, lithium manganate, lithium nickel manganate, composite metal oxides, and polyanion olivine type positive electrodes.

[0103] The negative electrode active material is not particularly limited as long as it can reversibly absorb and release lithium ions, remove and insert (intercalate) lithium ions, or dope and dedope counter anions of the lithium ions. Specific examples include lithium metal, carbon-based materials such as graphite, hard carbon, and soft carbon, metals that can form alloys with lithium such as aluminum, silicon, and tin, amorphous oxides such as silicon oxide and tin oxide, and lithium titanate.

[0104] <Solid electrolyte layer> The sulfide solid electrolyte powder according to the present embodiment may be used in a solid electrolyte layer. That is, the solid electrolyte layer according to the present embodiment contains the sulfide solid electrolyte powder described in the above <Sulfide solid electrolyte powder>, and preferred aspects of the sulfide solid electrolyte powder are also similar to those described in the above <Sulfide solid electrolyte powder>.

[0105] The solid electrolyte layer according to this embodiment is preferably used in a lithium ion secondary battery. Furthermore, the solid electrolyte layer according to this embodiment may contain a binder, if necessary.

[0106] The content of the sulfide solid electrolyte powder in the solid electrolyte layer according to the present embodiment is not particularly limited and may be appropriately determined depending on the performance of the target battery. For example, the content of the sulfide solid electrolyte powder is preferably 80 mass% or more, more preferably 90 mass% or more, relative to the entire solid electrolyte layer.

[0107] Examples of binders that can be contained in the solid electrolyte layer include butadiene rubber (BR), acrylate butadiene rubber (ABR), styrene butadiene rubber (SBR), polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), etc. The content of the binder in the solid electrolyte layer may be the same as that of a conventional binder.

[0108] The thickness of the solid electrolyte layer is not particularly limited and may be appropriately determined depending on the performance of the intended battery. For example, the thickness is preferably 10 to 50 μm, more preferably 15 to 20 μm. Here, from the viewpoint of obtaining a solid electrolyte layer having increased mechanical strength, resistance to stress such as vibration and bending, and high reliability, the thickness is preferably 10 μm or more, more preferably 15 μm or more. Moreover, from the viewpoint of increasing the ion conductivity between the positive and negative electrodes and increasing the energy density of the battery, the thickness is preferably 50 μm or less, more preferably 20 μm or less.

[0109] The method for forming the solid electrolyte layer is not particularly limited. For example, the components constituting the solid electrolyte layer described above are dispersed or dissolved in a liquid medium to form a slurry, which is then coated in a layer (sheet), dried, and optionally pressed to form the solid electrolyte layer. If necessary, a binder removal treatment may be performed by applying heat. The thickness of the solid electrolyte layer can be easily adjusted by adjusting the coating amount of the slurry, etc.

[0110] Instead of the wet molding as described above, the solid electrolyte layer may be formed by dry press molding of a solid electrolyte powder or the like on the surface of the object (positive electrode, negative electrode, etc.) on which the solid electrolyte layer is to be formed. Alternatively, the solid electrolyte layer may be formed on another substrate, which is then transferred to the surface of the object on which the solid electrolyte layer is to be formed. From the viewpoint of being able to industrially and stably form a strong solid electrolyte layer on the surface of the object on which the solid electrolyte layer is to be formed, it is preferable to form the solid electrolyte layer on the surface of the object by wet molding using a liquid medium.

[0111] <Lithium-ion secondary battery> The sulfide solid electrolyte powder according to the present embodiment may be used in a lithium ion secondary battery. That is, the lithium ion secondary battery according to the present embodiment includes the sulfide solid electrolyte described in the above <Sulfide solid electrolyte powder>, and preferred aspects are also the same.

[0112] The lithium ion secondary battery according to the present embodiment includes a solid electrolyte layer, a positive electrode layer, and a negative electrode layer. The sulfide solid electrolyte powder may be contained in at least one of the solid electrolyte layer, the positive electrode layer, and the negative electrode layer, or may be contained in at least two of the solid electrolyte layer, the positive electrode layer, and the negative electrode layer, or may be contained in all of the solid electrolyte layer, the positive electrode layer, and the negative electrode layer. Other than the sulfide solid electrolyte powder, the solid electrolyte layer, the positive electrode layer, and the negative electrode layer may be made of any of the conventionally known materials. EXAMPLES

[0113] The present invention will be specifically described below with reference to examples, but the present invention is not limited thereto. Examples 1 to 8 are examples, and Example 9 is a comparative example.

[0114] <Test Example> (Example 1) Under a dry nitrogen atmosphere, Li 5.4 P.S. 4.4 Cl 0.8 Br 0.8 Lithium sulfide powder (Sigma, purity 99.98%), diphosphorus pentasulfide powder (Sigma, purity 99%), lithium chloride powder (Sigma, purity 99.99%), and lithium bromide powder (Sigma, purity 99.995%) were weighed out to obtain the composition, placed in a heat-resistant container, and dissolved at 750°C for 1 hour under an atmosphere of gas containing sulfur element, and then cooled to room temperature at 5°C / sec to obtain a sulfide solid electrolyte. The gas containing sulfur element was a mixed gas of sulfur gas (Sx (x = 2 to 8)) and nitrogen gas (N2 gas) as a carrier gas, and the content of sulfur gas in the mixed gas was 10% by volume. The obtained sulfide solid electrolyte was coarsely pulverized with a cutter mill and adjusted to an average particle size (D50) of 10 to 20 μm, and then passed through a 100 μm mesh to obtain a coarsely pulverized sulfide solid electrolyte. Next, 200 g of the coarsely pulverized material obtained above was placed in a 1.0 L carbon container and placed in an electric furnace with a heating area and a cooling area. In the heating area, the coarsely pulverized material was heated at 430° C. for 15 minutes while circulating N2 gas at 10 L / min. The material was then moved to the cooling area at room temperature and cooled while circulating N2 gas at 20 L / min to obtain a non-agglomerated powder. The powder obtained above was added to 385 g of dehydrated dibutyl ether to obtain a slurry (slurry solid content: 30% by mass). 550 g of the slurry and 468 g of zirconia beads (Niccato Corporation, YTZ-0.3) with a diameter of 0.3 mm were placed in a zirconia sample container (vessel), which was then set in a Labostar Mini LMZ015 (Ashizawa Finetech Co., Ltd.) and wet-pulverized using a bead mill. Thereafter, the mixture was heated at a temperature equal to or higher than the boiling point of the solvent in a nitrogen atmosphere and dried to obtain a sulfide solid electrolyte powder.

[0115] (Examples 2 to 5) A sulfide solid electrolyte powder was obtained in the same manner as in Example 1, except that the peripheral speed and the grinding time among the wet grinding conditions using a bead mill were appropriately changed so that the specific surface area of ​​the obtained sulfide solid electrolyte powder would have the value shown in Table 1.

[0116] (Example 6, Example 7) A sulfide solid electrolyte powder was obtained in the same manner as in Example 1, except that high-purity Al2O3 beads (diameter 0.3 mm, Taimei Chemical, TB-03, purity 99.99% or more) were used instead of zirconia beads during wet grinding using a bead mill, and the peripheral speed and grinding time among the wet grinding conditions using a bead mill were appropriately changed so that the specific surface area of ​​the obtained sulfide solid electrolyte powder would have the value shown in Table 1.

[0117] (Example 8) Under a dry nitrogen atmosphere, Li 5.4 P.S. 4.4 Cl 0.8 Br 0.8 Instead of the composition of Li 5.4 P.S. 4.4 Cl 1.6 and the peripheral speed and the grinding time among the wet grinding conditions using a bead mill were appropriately changed so that the specific surface area of ​​the resulting sulfide solid electrolyte powder would have the value shown in Table 1. A sulfide solid electrolyte powder was obtained in the same manner as in Example 1.

[0118] (Example 9) Under a dry nitrogen atmosphere, Li 5.4 P.S. 4.4 Cl 0.8 Br 0.8 Lithium sulfide powder (Sigma, purity 99.98%), diphosphorus pentasulfide powder (Sigma, purity 99%), lithium chloride powder (Sigma, purity 99.99%), and lithium bromide powder (Sigma, purity 99.995%) were weighed out to obtain the above composition, mixed in a mortar, and then further mixed using a planetary ball mill (Ito Seisakusho, LP-M2) to obtain a sulfide precursor. The sulfide precursor powder was then calcined by heat treatment at 400°C for 5 hours in a dry nitrogen gas atmosphere, and then cooled to room temperature at a rate of 1°C / sec to obtain a coarsely pulverized sulfide solid electrolyte. The subsequent procedures were the same as those in Example 1, except that the peripheral speed and the grinding time among the wet grinding conditions using a bead mill were appropriately changed so that the specific surface area of ​​the resulting sulfide solid electrolyte powder would have the value shown in Table 1, to obtain a sulfide solid electrolyte powder.

[0119] <Evaluation> [Lithium ion conductivity] The sulfide solid electrolyte powder was pressed under a pressure of 380 MPa and used as a measurement sample. Measurements were carried out under the following conditions using an AC impedance measuring device (potentiostat / galvanostat VSP, manufactured by Bio-Logic Sciences Instruments). Measurement frequency: 100Hz~1MHz Measurement voltage: 100mV Measurement temperature: 25℃ From the obtained Nyquist plot, the lithium ion conductivity at 25° C. was calculated. The results are shown in Table 1.

[0120] [Crystal structure, crystallinity, distortion value, crystallite size] The sulfide solid electrolyte powders were measured by X-ray diffraction (XRD), and it was confirmed that all the obtained sulfide solid electrolytes contained a crystalline phase having an argyrodite-type crystal structure. For the XRD measurement, Si powder was mixed as an internal standard for each sulfide solid electrolyte powder, and an X-ray diffraction measurement (Rigaku Corporation, SmartLab) was used with a holder that was not exposed to the atmosphere. The obtained XRD pattern was refined by the Rietveld method using RIETAN-FP software. The analysis determined the structure with the lowest Rwp value as the crystal structure of each example. The Rwp value is the reliability factor Rwp (R-weighted pattern), which is a general guideline for the entire analysis range in fitting structure refinement by Rietveld analysis. The lower the Rwp value, the better, and in this analysis, the lowest Rwp value was less than 10%. This allowed us to determine the crystallinity (mass%) of the argyrodite-type crystals in the sulfide solid electrolyte powder, that is, the ratio of the crystalline phase to the total of the crystalline phase and the amorphous phase. The results are shown in Table 1.

[0121] In addition, the results obtained from the above analysis were analyzed using the Williamson-Hall method to determine the strain value and crystallite size. The method of calculation was to extract each peak value (2θ) and full width at half maximum (β) and convert them to 2sinθ / λ1 and βcosθ / λ1, respectively, where λ1 is the wavelength of CuKα1 radiation / Å, which is 1.5405. The obtained 2sinθ / λ1 and βcosθ / λ1 were plotted on the X-axis and Y-axis, respectively, and only the peaks derived from the argyrodite-type crystal structure were plotted. The slope of the linear approximation line of the obtained plot was taken as the distortion value, and the reciprocal of the intercept with the Y-axis was taken as the crystallite size, and each value was obtained. The results are shown in Table 1.

[0122] The XRD measurement conditions are as follows. Radiation source: CuKα radiation (λ=1.5418 Å (CuKα1 radiation wavelength 1.5405 Å, CuKα2 radiation wavelength 1.5443 Å, intensity ratio Kα2 / Kα1=0.497)), tube voltage: 45 kV, tube current: 200 mA, scan angle: 10-120°, scan speed: 5° / min, number of steps: 0.01° / step.

[0123] [BET specific surface area] BET specific surface area (specific surface area, m 2 / g) was measured, and the results are shown in Table 1.

[0124] [Distortion parameters] From the strain value and BET specific surface area obtained above, [(strain value - 0.001) / specific surface area (m 2 The value expressed as × 100 was calculated. The results are shown in Table 1.

[0125] [Battery evaluation] The resulting sulfide solid electrolyte powder: LiNi coated with lithium niobate with an average particle size of 7 μm 1 / 3 Co 1 / 3 Mn 1 / 3 O2 particles (positive electrode active material):conductive assistant:binder = 1.1g:5.0g:0.1g:0.6g ratio was mixed and stirred in butyl butyrate solution to obtain a slurry. The above slurry was applied onto an Al foil current collector by a blade method using an applicator, and vacuum dried at 80°C for 4 hours to obtain a positive electrode sheet. The obtained sheet was punched out with a die with a diameter of 10 mm to obtain a positive electrode mixture. On the other hand, a compact (diameter 10 mm, thickness 1 mm) of the obtained sulfide solid electrolyte powder was prepared, the positive electrode mixture was placed on the compact, and pressed at 500 MPa, after which a Li-In alloy was attached to the counter electrode. Then, the compact was restrained at a restraining pressure of 10 MPa or 100 MPa to prepare a lithium ion secondary battery (half cell). The half cell has a structure in which the contents are not exposed to the atmosphere.

[0126] The half-cell obtained was measured at 25°C and 4.3 to 2.5 V vs. Li + Charge and discharge were repeated five times in the range of / Li. The charge and discharge rates were both 0.1C. At the 6th cycle, 4.3V vs. Li at 0.1C rate + After charging to 1.5V / Li, the voltage is 1.9V vs. Li at 1C. + / Li, and the discharge capacity at that time was determined.

[0127] The ratio of the discharge capacity of the half-cell with a confining pressure of 10 MPa to the discharge capacity of the half-cell with a confining pressure of 100 MPa was determined. The results are shown in Table 1, where the discharge capacity ratio is normalized. Specifically, the discharge capacity ratio of Example 9 is normalized to be 1.00. The larger the normalized discharge capacity ratio is compared to Example 9, the better the interfacial contact with the active material can be maintained even when the confining pressure is low.

[0128] [Composite Modulus] The composite elastic modulus of the sulfide solid electrolyte powder obtained in Example 1 was determined. Specifically, 0.1 g of the sulfide solid electrolyte powder was molded into a compact (pellet) having a diameter of 10 mm. This compact was produced by applying pressure so that the relative density became 90%, and the sample of Example 1 was molded by applying a pressure of 570 MPa. A nanoindentation test was performed on the above pellet using a spherical indenter with a tip radius of 100 μm. As a result, it was confirmed that the composite elastic modulus of Example 1 was 11 GPa. Note that all samples were handled and measured in an environment not exposed to the atmosphere.

[0129] [Table 1]

[0130] As shown in Table 1, by obtaining a sulfide solid electrolyte by using a melting method, and then sequentially carrying out coarse pulverization using a cutter mill, heat treatment while suppressing aggregation, and fine pulverization using a bead mill, the distortion value can be increased without excessively reducing the particle size of the obtained sulfide solid electrolyte powder, and the ratio of [(distortion value - 0.001) / specific surface area (m 2 This resulted in a large value, expressed as the ratio of lithium ion conductivity (x1 / g) × 100. As a result, even when a lithium ion battery was assembled under a low confining pressure of 10 MPa, good interfacial contact was achieved, and good battery characteristics were achieved even after repeated charge-discharge cycles, without reducing the lithium ion conductivity of the sulfide solid electrolyte powder.

Claims

1. A sulfide solid electrolyte powder having a crystalline phase, [(distortion value - 0.001) / specific surface area (m 2 / g)]×100 is 0.010 to 0.

070.

2. Further having an amorphous phase, The sulfide solid electrolyte powder according to claim 1, wherein the content of the amorphous phase is 5 mass% or more.

3. The sulfide solid electrolyte powder according to claim 1, wherein the composite elastic modulus is 5 to 20 GPa.

4. An electrode mixture comprising the sulfide solid electrolyte powder according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Positive electrode active substance for all solid-state lithium secondary battery

    WO2019044733A1

  • Positive electrode active substance for all solid-state lithium secondary battery

    WO2019044734A1

  • Solid electrolyte, and electrode mixture, solid electrolyte layer and solid-state battery, each using same

    WO2021085239A1